Cortical Gyrification Morphology in ASD and ADHD: Implication for Further Similarities or Disorder-Specific Features?. (21st September 2021) - Gharehgazlou, Avideh; Vandewouw, Marlee; Ziolkowski, Justine; Wong, Jimmy; Crosbie, Jennifer; Schachar, Russell; Nicolson, Rob; Georgiades, Stelios; Kelley, Elizabeth; Ayub, Muhammad; Hammill, Christopher; Ameis, Stephanie H; et al.
Abstract: Shared etiological pathways are suggested in ASD and ADHD given high rates of comorbidity, phenotypic overlap and shared genetic susceptibility. Given the peak of cortical gyrification expansion and emergence of ASD and ADHD symptomology in early development, we investigated gyrification morphology in 539 children and adolescents (6–17 years of age) with ASD (n=197) and ADHD (n=96) compared to typically developing controls (n=246) using the local Gyrification Index ( l GI) to provide insight into contributing etiopathological factors in these two disorders. We also examined IQ effects and functional implications of gyrification by exploring the relation between l GI and ASD and ADHD symptomatology beyond diagnosis. General Linear Models yielded no group differences in l GI, and across groups, we identified an age-related decrease of l GI and greater l GI in females compared to males. No diagnosis-by-age interactions were found. Accounting for IQ variability in the model (n=484) yielded similar results. No significant associations were found between l GI and social communication deficits, repetitive and restricted behaviours, inattention or adaptive functioning. By examining both disorders and controls using shared methodology, we found no evidence of atypicality in gyrification as measured by the l GI in these conditions.